PERFORMANCE IMPROVEMENT IN INTERSUBSPECIFIC HYBRIDS OF RICE - J. K. Goncharova; E. M. Кharitonov (Вавиловский журнал генетики и селекции, 2014)
It is known that heterotic hybrids surpass traditionally bred varieties in productivity by 30–40 %; moreover, they are often more adaptive, resistant to diseases, and able to produce a stable yield. The possibility of raising intersubspecific rice hybrids is discussed. Particular attention is given to localization of wide compatibility (WC) genes in the rice genome and prospects of using molecular markers for introgression of WC genes into Russian varieties. Analysis of hybrid sterility in several Russia-bred varieties has revealed no WC genes, defining large seed sets of hybrids.